Dengue virus type 2 envelope protein displayed as recombinant phage attachment protein reveals potential cell binding sites - Abd-Jamil, Juraina; Cheah, Chen Yee; AbuBakar, Sazaly (Oxford University Press, 2008)
A method to map the specific site on dengue virus envelope protein (E) that interacts with cells and a neutralizing antibody is developed using serially truncated dengue virus type 2 (DENV-2) E displayed on M13 phages as recombinant E-g3p fusion proteins. Recombinant phages displaying the truncated E consisting of amino acids 297-423 (EB2) and amino acids 379-423 (EB4) were neutralized by DENV-2 patient sera and the DENV-2 E-specific 3H5-1 monoclonal antibodies suggesting that the phages retained the DENV-2 E antigenic properties. The EB4 followed by EB2 recombinant phages bound the most to human monocytes (THP-1), African green monkey kidney (Vero) cells, mosquito (C6/36) cells, ScFv specific against E and C6/36 cell proteins. Two potential cell attachment sites were mapped to loop I (amino acids 297 to 312) and loop II (amino acids 379-385) of the DENV-2 E using the phage-displayed truncated DENV-2 E fragments and by the analysis of the E structure. Loop II was present only in EB4 recombinant phages. There was no competition for binding to C6/36 cell proteins between EB2 and EB4 phages. Loop I and loop II are similar to the sub-complex specific and type-specific neutralizing monoclonal antibody binding sites, respectively. Hence, it is proposed that binding and entry of DENV involves the interaction of loop I to cell surface glycosaminoglycan-motif and a subsequent highly specific interaction involving loop II with other cell proteins. The phage displayed truncated DENV-2 E is a powerful and useful method for the direct determination of DENV-2 E cell binding sites.